Investigation on Deformation Mechanism and Treatment Effect of a Scattered Slope Based on Continuum–Discontinuum Element Method and Finite Difference Method - Gao, Meiben; Zhang, Hua; Cui, Shenghua; Wu, Zhongteng; Liu, Ji; Feng, Lixia; Zeng, Feng; Li, Ning; Chen, Fujiang; Li, Tianbin; Zhang, Yan (Frontiers in Earth Science, 2022)
Slope deformation and failure is an inevitable engineering problem in highway construction and operation in mountainous areas. Its essence is a continuous-discontinuous gradual failure process of slope under the action of unbalanced force. Slope deformation and failure mechanism is the basis and key content of its emergency treatment and comprehensive treatment. In this paper, the continuous discontinuous element method (CDEM) and finite difference method are used to analyze the deformation mechanism and supporting effect of a scattered slope in Biwei Expressway. The results show that the change of local geological environment caused by roadbed excavation leads to slope slippage along the surface, and then pulls the upper rock mass gradually to produce slippage failure, resulting in the stability gradually decreases. The mechanism is traction sliding-tensile cracking. The continuous discontinuous element method can effectively simulate the formation process of the main and sub sliding planes during excavation, and can better display the phenomenon of slope failure and gradual disintegration. Emergency disposal of gravity anti-sliding retaining wall in front of the slope can effectively control further deformation and ensure temporary stability. In comprehensive treatment, step-type slope excavation, gravity anti-sliding retaining wall and anchor frame beam are adopted to control the deformation and failure of slope and ensure long-term stability. The numerical simulation results are consistent with the actual results, which effectively explains the rationality of this study. The research results of this paper can provide some reference for the emergency treatment and comprehensive treatment of slope in mountainous areas, and for the construction and operation of highway and other infrastructure in mountainous areas.